Impact of Battery Degradation on Lifetime Ranges of Electric Aircraft and Unmanned Underwater Vehicles - Paek, Sung Wook; Rayappan, Christober Vinoth Raj; Kim, Sangtae (2019 3RD IEEE CONFERENCE ON CONTROL TECHNOLOGY AND APPLICATIONS (IEEE CCTA 2019), 2019)
Electrification of mobility is now extending toward air and sea transportation beyond ground electric vehicles. However, electric aircraft must carry its battery weight to fly and electric ships must overcome water frictions far greater than atmospheric drag, leading to much shorter travel distances than fossil fuel counterparts as well as ground electric vehicles. From operating perspectives, airlines or ferry operators might suffer high maintenance costs if batteries age rapidly and must be replaced often. This paper uses the optimal range formulas for electric aircraft and underwater vehicles to assess the impact of various battery-aging patterns on the lifetime accumulated ranges. It is found that the magnitude of the slope of a battery capacity curve must be small near the end of life to maximize the lifetime range. Also, this total range is more sensitive to degradation patterns in underwater vehicles which have higher proportions for non-propulsive power than electric aircraft. The insight could be used to design economical batteries for electric transportation businesses, and the follow-up work will upscale this work to the modeling of hybrid-electric aircraft and ships.